English abbreviations related to language teaching: problems of typology and translation into Ukrainian - N. Kovalchuk (Викладання мов у вищих навчальних закладах освіти на сучасному етапі: Міжпредметні зв'язки)
The article analyses the thematic groups (TG) and subgroups (SG) of English language abbreviations of four categories related to language teaching: 1) names of language teaching organisations; 2) names of approaches to language teaching and forms of its organisation; 3) names of forms of control, diplomas and certificates in language teaching; 4) characteristics of languages as objects of study and learners. On the basis of similar studies on thematic classification of Ukrainian language terminology, the author claims the insufficient number of studies on English language abbreviations. This, together with the need for their systematic thematic classification, has made it possible to substantiate the relevance of the study. The aim of the study is to identify the above-mentioned TGs and TPGs, to determine their structural characteristics and methods of translation. Consequently, the tasks included the selection of research material, its analysis, the formulation of conclusions and further perspectives. The criterion for distinguishing between TGs and TPGs is the denotative feature, which signifies the realities of extra-linguistic reality. The division of lexemes into TGs and TPGs is an important task in the study of the terminological system. The material of the study included 435 abbreviations selected from original English sources. Within the categories analysed, TGs and TPGs have different degrees of branching and can each contain from 1 to 7 groups and subgroups. The latter can be further subdivided into even smaller units. As a result, the largest and most ramified TGs and TPGs are located in the centre of each category, while the smallest are on the periphery. The analysed TGs and TPGs differ in terms of their quantitative composition, structural models, belonging to a part of speech and the principles of rendering English abbreviations into Ukrainian. The logic and clarity of the analysed TGs and TPGs are ensured by the common conceptual features of their components, which give the respective TGs and TPGs their thematic integrity. These components are based on different models of term formation, which may influence the techniques chosen to translate them. The study of such dependencies within the analysed categories is suggested as a prospect for further research.